-8m-8n+p-2=-10n-9p+8

Simple and best practice solution for -8m-8n+p-2=-10n-9p+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8m-8n+p-2=-10n-9p+8 equation:


Simplifying
-8m + -8n + p + -2 = -10n + -9p + 8

Reorder the terms:
-2 + -8m + -8n + p = -10n + -9p + 8

Reorder the terms:
-2 + -8m + -8n + p = 8 + -10n + -9p

Solving
-2 + -8m + -8n + p = 8 + -10n + -9p

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + -8m + -8n + 2 + p = 8 + -10n + 2 + -9p

Reorder the terms:
-2 + 2 + -8m + -8n + p = 8 + -10n + 2 + -9p

Combine like terms: -2 + 2 = 0
0 + -8m + -8n + p = 8 + -10n + 2 + -9p
-8m + -8n + p = 8 + -10n + 2 + -9p

Reorder the terms:
-8m + -8n + p = 8 + 2 + -10n + -9p

Combine like terms: 8 + 2 = 10
-8m + -8n + p = 10 + -10n + -9p

Add '8n' to each side of the equation.
-8m + -8n + 8n + p = 10 + -10n + 8n + -9p

Combine like terms: -8n + 8n = 0
-8m + 0 + p = 10 + -10n + 8n + -9p
-8m + p = 10 + -10n + 8n + -9p

Combine like terms: -10n + 8n = -2n
-8m + p = 10 + -2n + -9p

Add '-1p' to each side of the equation.
-8m + p + -1p = 10 + -2n + -9p + -1p

Combine like terms: p + -1p = 0
-8m + 0 = 10 + -2n + -9p + -1p
-8m = 10 + -2n + -9p + -1p

Combine like terms: -9p + -1p = -10p
-8m = 10 + -2n + -10p

Divide each side by '-8'.
m = -1.25 + 0.25n + 1.25p

Simplifying
m = -1.25 + 0.25n + 1.25p

See similar equations:

| 12*x^2-4=0 | | t(2t+-1)=1 | | 10-(4x-1)=8-5x | | 7x+21(2x-3)=180 | | 8c*3c= | | 3x+22x-4=5(5x+6) | | (-7b+4a)+(-6a-9b)= | | 5w^2+39w+5y=0 | | 9a+19=100 | | X^2-2x+528=0 | | 98=-2(-8x+8) | | 8cos^2x-4cosx-2=0 | | 6g=6g+-34 | | 3x+x+7=6x-2x+7 | | 0.25d+6=11 | | =5x | | N-3.5=6.5 | | 9f+15=15 | | (xy^2+y)dx+(x^2y-x)dy=0 | | 3+x/2=10 | | 8=4(b-2)+4 | | 32=-5x-8 | | 12(2p+11)=12(2p+12) | | 4x+12x-7=4(4x+9) | | -1=-2y+7 | | -15=9-8x | | 8=(b-2)+4 | | 5-6(2+6)=b-14 | | 4.75m+15=2.75m+6 | | -4(x+1)+3(3x-3)=4(x-4)+12 | | 2n+8=5n-10 | | 40x/40=14/40 |

Equations solver categories